Applied biocatalysis : the chemist's enzyme toolbox - Whittall, John; Sutton, Peter (John Wiley & Sons, Inc., 2021)
"Biocatalysis has had a significant impact on the synthesis of active pharmaceutical ingredients (APIs) in recent years. The main driver for this is the ability to harness the regio- and stereoselectivity of enzymes to improve the efficiency of synthetic routes. For example, enzymes can offer direct access to enantiopure products, where traditional organic synthesis would require either resolution or the use of auxiliary groups [1], whilst applied enzymes have improved syntheses or generated molecules that would otherwise be either impossible or impractical to synthesise."-- Provided by publisher
Keywords: Biocatalysis.; elektronické knihy; electronic books